DRUG THERAPY OF OSTEOPOROSIS - Dr VAIBHAVI ACHAREKAR; Dr PRAMILA YADAV; Dr MERLYN GOMES (International Journal of Pharma and Bio Sciences, 2016)
Osteoporosis is a highly prevalent condition characterized by decreases in bone mass and micro architectural alterations. Bone fractures, especially of the hip and vertebrae, are the most burdensome complications of osteoporosis. The gold standard imaging technique of diagnosing Osteoporosis is Digital X-ray Absorptiometry because it shows best predictive value for fracture risk. Lifestyle intervention for osteoporosis includes regular weight-bearing exercise and avoidance of unhealthy behavior, such as cigarette smoking and excess alcohol intake.The drugs used are either those inhibiting bone resorption and those stimulating bone formation and both. Numerous drugs are currently available to treat osteoporosis, such as Bisphosphonates, Strontium ranelate and others and the choice of a specific compound should be guided by efficacy and safety considerations.